Shaping the tumor microenvironment with Modified Vaccinia Virus Ankara and TLR9 ligand - Préville, Xavier (Oncoimmunology, 2015)
Our preclinical data demonstrate that an intravenous injection of Modified Vaccinia virus Ankara induces CD8(+) lymphocytes to infiltrate organs to control the growth of orthotopic renal carcinoma upon combination with a toll-like receptor 9 agonist. Such shaping of the tumor microenvironment could constitute the basis of more effective clinical protocols of tumor immunotherapy.